PENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING DALAM PENINGKATAN PEMBELAJARAN IPA - aji pamungkas, weka (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract : The UseModel Of Contextual Teaching And Learning In Improving SainsLearning In Fourth Grade Student.This study aims to: describe the process of learning and increase learning Sains.Fourth grade students study subjects SDN 5 Kebumen. Based on theresults of the research studyquality increased from the firstcycle, second cycle and third cycle. I suklusstudent activity 68,82%, the second cycle is 80,15% can be concludedin the first cycle showed an increase compared to the prior action. Beforethe action of students scoring above the KKM (75)is 18 students or46,15% with anaverage value of 63. In the first cycle of students who scored above KKM(75) is 25students or 64,10%with an average of 72,69% in the second cycle 71,79% and third cycle reaches100%.Keywords: contextual teaching and learning, Sains, ImprovedLearning Abstrak:: Penggunaan Model Contextual TeachingAnd Learning dalam peningkatan pembelajaran IPA pada siswa kelas V SD. Penelitian ini bertujuan : mendeskripsikan proses pembelajaran dan peningkatan pembelajaran IPA. Metode yang digunakan adalahdengan menggunakan pendekatan ContextualTeaching and Learning. Subjek penelitian siswa kelas V SDN 5 Kebumen.Berdasarkan hasil penelitian kualitas pembelajaran mengalami peningkatan darisiklus I, siklus II, dan siklus III. Hal ini dapat dibuktikan dengan presentasepenilaian proses pada siklus I sebesar 63,3 % menjadi 79,8 % pada siklus II danmeningkat menjadi 83,6 pada siklus III. Perbandingan persentase ketuntasan belajar dari kondisi awal hanya 41,18%,meningkat menjadi 82,35 % pada siklus II meningkat lagi menjadi 88,23% dan padasiklus III memperoleh 94,12 %.  Kata Kunci: Contextual TeachingAnd Learning, IPA, PeningkatanPembelajaran